CRITICAL DISCOURSE ANALYSIS OF ONLINE NEWS IN THE MOLOTOV BOMB CASE IN SAMARINDA - Sri Hadijati; Widyatmike Gede Mulawarman; Bibit Suhatmadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze critical discourse in online media coverage of the Molotov cocktail incident in Samarinda using the approach of Norman Fairclough and Teun A. van Dijk. The data consists of three online news articles analyzed from the perspective of text, discursive practices, and social practices. The results show that all three articles tend to present narratives that support the police as the sole source and frame the perpetrators as a threat to public security. The demonstrations are reduced to potential anarchy, and the perpetrators are denied any opportunity to defend themselves. The analysis shows that the media plays a role as a reproducer of state power in constructing public opinion.